Aesthetic creation - Zangwill, Nick.; Oxford eBooks (Oxford : Oxford University Press, 2007)
What is the purpose of a work of art? What drives us to make art? Why do we value art and consume it? Nick Zangwill argues that we cannot understand the nature of art without first having answers to these fundamental questions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Art -- Philosophy; Electronic books